Numerical investigation of novel flow field configurations for direct methanol fuel cell. (2022) - P.M., Sutheesh; Jose, Jobin; Abraham, Libin; K., Manikandan
Abstract: Fuel cell performance is directly dependent on the flow field design on the cathode and anode plates. Flow field structure also affects the temperature distribution and flow velocity in electrode plates, which will indirectly affect the power output of the fuel cell. In this study, a new flow field design is compared with a conventional serpentine flow field. Flow pattern, temperature distribution, velocity distribution and pressure drop are estimated in both flow fields. Commercial Computational Fluid Dynamics (CFD) package is used to solve the numerical problem. Fuel pumping pressure required for different flow velocities is estimated in the new flow field design. Maximum temperature in the plate at different inlet velocity conditions is also estimated without considering the chemical reaction involved in the fuel cell. It is observed that the pressure drop increases with an increase in mass flow rate through channels also the new proposed flow field have lower pressure drop than the conventional serpentine flow field. For an inlet condition of 0.1 m/s velocity of methanol, a 91 % reduction in pressure drop is obtained. The maximum temperature on the plate decreases with an increase in flow velocity, 304.9 K is observed at the outlet of both serpentine and zig zag flow field for an inlet velocity condition of 0.004 m/s.